TRAZODONE FOR SLEEP DISTURBANCE DURING METHADONE MAINTENANCE: A DOUBLE-BLIND, PLACEBO-CONTROLLED TRIAL - Stein, Michael D. (2011)
BACKGROUND: To test whether trazodone, one of the most commonly prescribed medications for treatment of insomnia, improves subjective and/or objective sleep among methadone-maintained persons with sleep complaints, we performed a randomized, double-blind, placebo-controlled trial with six month follow-up. METHODS: From eight methadone maintenance programs in the northeastern United States, we recruited 137 persons receiving methadone for at least one month who reported a Pittsburgh Sleep Quality Index (PSQI) score of six or higher. Two-night home polysomnography (PSG) was completed at baseline and one month later, with morning surveys and urine drug toxicologies. Interviews assessed sleep over the past 30 days at baseline and 1-, 3-, and 6- month follow-ups. RESULTS: Participants averaged 38 years of age, were 47% male, and had a mean PSQI total score of 12.9 (± 3.1). At baseline, intervention groups did not significantly differ on 10 PSG-derived objective sleep measures and 11 self-reported measures. Over 88% (n = 121) of participants completed the PSG at 1-month. Without adjusting p-values for multiple comparisons, only 1 of 21 sleep measure comparisons was statistically significant (p<.05). The effect of trazodone on mean PSQI scores during the six-month follow-up was not statistically significant (p = .10). Trazodone neither significantly increased nor decreased illicit drug use relative to placebo. CONCLUSIONS: Trazodone did not improve subjective or objective sleep in methadone-maintained persons with sleep disturbance. Other pharmacologic and non-pharmacologic treatments should be investigated for this population with high rates of insomnia.